New information literacy for new learning environments: the impact of the web 2.0 - Lasić-Lazić, Jadranka (Array, 2009)
For several decades, the importance of information literacy as a cluster of competencies needed for managing learning processes and for learning independently in electronic environments has been recognized and acknowledged. In the last decade a new version of the Web has emerged that has changed the premises of learning in electronic environments by transforming the very nature of knowledge, information and learning. In this paper, we have questioned the way the Web 2.0 world should/would contribute to future models of information literacy. A valid starting point for redefining models are the changing patterns of information behavior, which were characterized in a range of studies, and changing attributes of learning environments, which show a clear tendency towards the web 2.0 philosophy of sharing, mixing, interaction, collaboration, participation. What will happen with information literacy now when the merits of e-learning have changed with the appearance of Web 2.0? Can information literacy remain unchanged? After drawing conclusion from reviewed and conducted studies the authors will draw possible scenarios and construct models of a new version of information literacy. These shifts in information literacy conceptions are needed in order to respond to changing paradigms in information behavior, learning and e-learning.